Development of an Electronic Supplementary Book on Water Pollution - Tya Daniela; Husna Amalya Melati; Erlina Erlina; Risya Sasri; Hairida Hairida; Ida Lestari (Universitas Pendidikan Mandalika, 2023)
Water pollution is a scientific study of environmental chemistry on the sources, impacts and fate of chemicals in the aquatic environment, as well as the effects of human activities on them. As a student, you are required to have broad insight and knowledge, especially in dealing with environmental problems in society, by creating a caring character of the environment and finding solutions as an effort to overcome these problems. The purpose of this study is to produce educational materials in the form of additional e-books about water pollution, raising real problems that exist in the surrounding community. In addition, feasibility test and student responses were also measured against the Electronic Supplement on Water Pollution Equipment. The method employed in this study is R&D with the ADDIE model. Research data were collected through speaker and student interviews, due diligence questionnaires and student response questionnaires. The results of the feasibility test conducted by the expert validator on the Electronic Supplementary Book on Water Pollution Material show that the feasibility test for material, language and graphics is 1.00 with a very high validity category. The results of student responses to the Electronic Supplement Book on Water Pollution Material in the limited trial produced a percentage of 86% in the very good category and field trials produced a percentage of 93%.